Analysis of Reaching the Lisbon Strategy Targets at the National Level: the Eu-27 and Slovenia - Aleksander ARISTOVNIK; Andrej PUNGARTNIK (Transylvanian Review of Administrative Sciences, 2009)
Adopted by the European Council in 2000, theLisbon Strategy is a long-term strategy and its maintarget is to make Europe the most competitive,dynamic and knowledge-based economy in theworld by 2010. During the 2005 mid-term review,the Lisbon Strategy refocused its two maintargets on economic growth and employment,and formally integrated the Cohesion policy into itsimplementation. In spite of the review, the effortsto meet the strategic targets have proven to beinsufficient both at the EU and Slovenian levels.While certain progress has been observed, thestrategy should be further adjusted, coordinatedand supplemented at the national and pan-European levels so that the Lisbon targets canbe attained. The article investigates the currentstage of the achievement of the targets, using thetime-distance method to calculate the time lead orlag in implementing the Lisbon Strategy targets atthe European Union and Slovenia levels.